RISK MANAGEMENT ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY IN LOADING AND UNLOADING PROCESSES ON PASSENGER SHIPS ALONG THE KIJANG–SUNGAI GUNTUNG ROUTE (CASE STUDY ON KM SABUK NUSANTARA 110) - Embun Febryanti Panggabean; Juliana Nasution (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the Occupational Safety and Health (OHS) risk management in the loading and unloading process on KM Sabuk Nusantara 110. The main focus of this study is to identify potential hazards, assess the level of risk, and evaluate the effectiveness of implementing safety procedures on the ship. Using qualitative methods, data were collected through in-depth interviews with chief engineers and stevedoring workers and related literature reviews. The results of the study identified several major potential hazards, such as the breaking of the crane steel rope due to excess load capacity, the risk of slipping due to the slippery ship floor, and the lack of worker awareness in using personal protective equipment (PPE). Although there have been no significant work accidents, the implementation of the OHS SOP still has weaknesses, especially in supervision and routine training for workers. Therefore, this study recommends increasing supervision of the use of PPE, preventive maintenance of equipment, and holding periodic training to increase worker awareness and compliance with safety procedures. These findings are expected to be the basis for formulating more effective occupational safety policies in the maritime sector.